Effect of stud shape on lower limb kinetics during football-related movements - Lv, X.; He, Y.; Sun, D.; Baker, J. S.; Xuan, R.; Gu, Y. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
Different football shoe designs used under the same turf condition can impact athletic performance and influence the risk of injury. The purpose of this study was to investigate the effect of different shape studs of football shoes on lower limb kinetics during straight-ahead running and 45° left sidestep cutting movements. Twelve male football players were recruited from university football teams. They were asked to perform six trials using straight-ahead running and a 45° left sidestep cutting movement on artificial turf while wearing football shoes with the following three stud configurations: knife stud, triangle stud and round stud. The contact time of knife stud was longer than triangle stud and round stud. In the straight-ahead running task, the ground force in the direction of movement of knife stud and round stud was lower than triangle stud. The peak pressure on the lateral forefoot (5 metatarsal region) in knife stud was higher than triangle stud and round stud in the cutting movements. The peak pressure and force-time integral on the medial (1 metatarsal region) and central (2-4 metatarsal region) forefoot in triangle stud were smaller than round stud. The different stud shapes of firm ground soccer shoes have little effect on the traction force. Knife stud has a higher risk of fifth metatarsal bone injury. The triangle stud shows good explosive force and provides the ability to change direction quickly. The round stud generally produces the minimum peak vertical ground reaction force and has a good capability of changing direction among the three shoes.